Financial Aspects of Digitalization in the Tourism Industry - ARTAMONOVA, Marina; BREDIKHINA, Olga; GUSEV, Valery; VOSKANYAN, Olga; GUCHOK, Zhanna; BUHTEEVA, Yulia (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).05, 2019)
Each large segment of the market is developing in digital technologies, using them in order to increase sales, brand awareness and create certain trends related to the activities of the company or organization. Tourism, as well as all other players on the world stage, considers digital technologies as the shortest and most effective way to its customers. In the field of tourism, digital promotion is especially important as the end user can be thousands of kilometers from the route of his journey. Today, 3.5 billion people have access to the Internet. This number includes people of all age groups, with different wages and social status. This indicator is growing every year. If earlier it was believed that the Internet is mainly used by young people, at the moment more and more adults and elderly people, especially abroad, use social networks every day and use the Internet to search for information.